2021
DOI: 10.1108/aaaj-08-2020-4793
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic accountability and the role of risk reporting during a global pandemic

Abstract: PurposeThis article lays out some conceptual considerations of how dynamic accountability and risk reporting practices could be tailored during and after a global pandemic.Design/methodology/approachThis conceptual paper seeks to foster the debate on the crucial role of risk reporting considering the impact and uncertainty caused by the coronavirus disease 2019 (COVID-19) pandemic and stakeholder information needs in this context. The authors draw upon neo-Durkheimian institutional and legitimacy theories and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 37 publications
(70 reference statements)
3
34
0
Order By: Relevance
“…However, studies on Covid-19 related corporate disclosures are very limited in accounting research. While the extant research covered issues of risk disclosures (Carnegie et al, 2022;Crovini et al, 2022), CSR reports (Albitar et al, 2021), reporting uncertainty (Elmarzouky et al, 2021) and…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies on Covid-19 related corporate disclosures are very limited in accounting research. While the extant research covered issues of risk disclosures (Carnegie et al, 2022;Crovini et al, 2022), CSR reports (Albitar et al, 2021), reporting uncertainty (Elmarzouky et al, 2021) and…”
Section: Discussionmentioning
confidence: 99%
“…The quality of disclosure is low. The study of Crovini et al (2022) pointed out a few conceptual considerations of how dynamic accountability and risk reporting could be connected during and after the pandemic. The authors recommended that organizations understand the changing information needs of the stakeholders during this time and link risk reporting to their business models.…”
Section: Covid 19 and Accounting Research: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivations of this study are linked to the primary and urgent need to assess the current state of corporate reporting practices affected by the pandemic crisis by identifying and highlighting possibilities for changing some sustainability disclosure practices that could be useful for preparers, users, regulators and policymakers. As some previous studies confirmed, this unexpected and very critical situation may benefit the business context by pushing some changes on ESG issues to improve the corporate reporting transparency and to move toward more accountability based reporting practices by satisfying new information needs (Crovini et al, 2022 ; Hassan et al, 2021 ; Leoni et al, 2021 ; Lodhia et al, 2021 ; Rinaldi, 2022 ).…”
Section: Introductionmentioning
confidence: 96%
“…Other impacts such as liquidity risk have become a major challenge for small and large companies, because economic activity and business models have almost stopped. There is a concern that companies will reduce their policies and initiatives on CSR activities to support sustainability as the activities also require costs [7].…”
Section: Introductionmentioning
confidence: 99%